Pengaruh Kegiatan Peningkatan Minat Baca Diera Digitalisasi, dengan menggunakkan E-Book Secara Gratis di SMP Negeri 3 Tasik Payawan di Desa Hiang Bana - Aisya Fadila; Akmal Adib Rahman; Dendi Fransisko; Hefi Hefi; Jefny Afshera; Julita Julita; Leo Arya P; Maya Anggraini C; Messy Messy; Rana Mustika; Silvi Melinatha; Stefanya Ketauraceta; Yayu Yayu; Yeheski Andre D; Murniyati Yanur (Panggung Kebaikan : Jurnal Pengabdian Sosial, 2024)
This journal discusses the influence of activities to increase interest in reading in the era of digitalization, by using free e-books at SMP Negeri 3 Tasik Payawan in Hiang Bana Village. Interest in reading is a basic element in developing individual literacy. Literacy does not focus on aspects of reading and writing, but on the skills to understand, analyze and interpret information conveyed through writing. This socialization aims to increase reading interest in using e-books so that students can use them easily in the current era of digitalization. This activity was carried out by the KKN 105 team at Palangka Raya University. The socialization activity was held on Wednesday, August 7 2024. The activity started at 07.30 WIB until finished. Results and discussion of the implementation of activities by the Palangka Raya University KKN 105 team for Tasik Payawan Middle School 3 students with socialization regarding increasing students' interest in reading in the era of digitalization, using e-books for free can provide positive benefits and value for socialization participants, especially Tasik Payawan Middle School 3 students. After the socialization was held, the KKN team together with Class IX students formed a reading community via the social media WhatsApp. The aim of forming this community is for KKN students to be able to provide more detailed explanations that were not given during the socialization. This forum is also used as a medium for distributing various quality and enjoyable e-books to female students. It is hoped that with this socialization and the formation of a reading community, students' access to reading sources will become wider, students' interest in reading will increase, literacy levels will increase and the quality of human resources for the next generation of young people will improve.